2008+ solved problems in electromagnetics - Nasar, S. A. (SciTech Publishing, 2008)
This book covers the following areas: vector analysis; electrostatics; magnetostatics; Maxwell's equation; plane waves; transmission lines; waveguides; cavity resonator; and antenna.